2014
DOI: 10.2106/jbjs.l.00698
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Coronoid Process Using the Tip of the Ipsilateral Olecranon

Abstract: Reconstruction of the coronoid using the tip of the ipsilateral olecranon was an effective method for restoring normal kinematics over a range of elbow motion from 20° to 120° in a cadaveric model of an elbow with a 40% coronoid deficiency. This reconstruction technique may prove beneficial for patients with elbow instability due to coronoid deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Alolabi et al showed that reconstruction of the coronoid using the tip of the ipsilateral olecranon was an effective method for restoring normal kinematics over a range of elbow motion from 20 to 120 in a cadaveric model of an elbow with a 40% coronoid deficiency. 39…”
Section: Functional Anatomy Of the Proximal Ulna In Relationship To Elbow Stabilitymentioning
confidence: 99%
“…Alolabi et al showed that reconstruction of the coronoid using the tip of the ipsilateral olecranon was an effective method for restoring normal kinematics over a range of elbow motion from 20 to 120 in a cadaveric model of an elbow with a 40% coronoid deficiency. 39…”
Section: Functional Anatomy Of the Proximal Ulna In Relationship To Elbow Stabilitymentioning
confidence: 99%
“…Only a biomechanical in vitro study conducted by Alolabi et al 1 showed the possibility of properly correcting the technique by modifying the direction of the osteotomy, but to date clinicians do not have proper clinical outcomes to recommend this procedure. However, using a healthy portion of an unstable elbow to make it stable again should be accurately planned before starting the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…They found that excision of 50% of the olecranon exerted no significant effect on elbow joint stability, including varus, valgus, and rotation. Alolabi et al 23 comparatively analyzed the biomechanics among the intact ulna, partial excision of the coronoid process (40%) and partial excision of the coronoid process (40%) combined. Ramirez et al 24 conducted a biomechanics experiment and obtained findings consistent with those of Alolabi et al 23 However, they made certain modifications, such as complete excision of the coronoid process and use of an identically sized olecranon osteotomy for reconstruction.…”
Section: Selection Of Reconstruction Materialsmentioning
confidence: 99%